Penguatan Komunikasi Kesehatan dan Kesehatan Mental sebagai Strategi Pencegahan Burnout pada Tenaga Kesehatan di Klinik Kota Bandung - Dedeh Dahliah; Mufti Fauzi Rahman; Nadia Ushfuri Amini; Ermilda Ermilda; Nur Rakhmanto Heryana; Yusuf Bukhori (Politeknik Negeri Cilacap, 2026)
This community service program is aimed to up the capacity of workers in clinics under the Indonesian Clinic Association (ASKLIN) of Bandung city with strengthening of health communication and mental health as an effort to prevent burnout. The activity was implemented on December 4th, 2025, at Bhakti Kencana University, and followed by 38 participant from various clinics in Bandung City. The methods used is seminars, workshops, role plays, and simulations with materials like effective communication of health, stress management, mindfulness and self-care technique. Based on he result of pre-test and post-test, this program showed that there is an increase of uderstanding from participant around 9.53% . It means that this program had a positive impact on increasing awareness and practical skills in preventing burnout of workers in clinical health service facilities. Keywords : health communication, mental health, burnout